Immune response to two hours of rowing in elite female rowers - Nieman, D. C.; Nehlsen-Cannarella, S. L.; Fagoaga, O. R.; Henson, D. A.; Shannon, M.; Davis, J. M.; Austin, M. D.; Hisey, C. L.; Holbeck, J. C.; Hjertman, J. M.; Bolton, M. R.; Schilling, B. K. (International Journal of Sports Medicine, 1999)
The influence of carbohydrate (C) versus placebo (P) beverage consumption on the immune and hormonal responses to normal rowing training sessions was measured in 15 elite female rowers residing at the U.S. Olympic Training Center. In a randomized, counterbalanced design, the athletes received C or P beverages (double-blind) before, during, and after two 2-hour bouts of rowing (one day apart). Blood samples were collected before, and 5-10 minutes and 1.5 hours after rowing. Metabolic measures indicated that training was performed at moderate intensities, with some high intensity intervals interspersed throughout the sessions (mean oxygen uptake of 2,307+/-169 m x min(-1), 57% of VO2max). Glucose and insulin were significantly lower after two hours of rowing with ingestion of P compared to C. The patterns of change in cortisol, growth hormone, epinephrine, and norepinephrine did not differ between C and P rowing trials. Blood neutrophil cell counts and the neutrophililymphocyte ratio were significantly higher following P versus C rowing sessions. The patterns of change in blood lymphocyte and lymphocyte subset counts, and lymphocyte proliferative responses did not differ between P and C trials, except for a slight difference in NK cell counts and activity. In summary, minimal changes in blood hormonal and immune measures were found following two-hour bouts of training in elite female rowers. Carbohydrate compared to placebo ingestion attenuated the moderate rise in blood neutrophil counts, but had slight or no effects on other immune parameters.